Origin(s) of Antarctica's Wilkes Subglacial Basin. Issue 4 (16th December 2013) - Weihaupt, John G.; Van Der Hoeven, Frans G.; Lorius, Claude; Chambers, Frederick B.
Abstract: The Wilkes Subglacial Basin (WSB), the largest subglacial basin in East Antarctica, is a topographic depression of continental proportions that lies beneath the East Antarctic continental ice sheet. Discovered by the US Victoria Land Traverse 1959–60, the origin of the WSB and the influence of palaeoclimate on its overlying continental ice sheet have remained uncertain since the time of its discovery. Most explanations of origin favour lithospheric structural control as a function of tectonic activity. Lithospheric flexure due to thermally or isostatically induced uplift of the Transantarctic Mountains was suggested in the 1980s. Lithospheric extension and rifting was proposed in the 1990s. More recent investigations have revealed the presence of fold and thrust belts, casting doubt on flexural and extensional hypotheses as the primary mechanisms, suggesting instead a compressional scenario. While remaining inconclusive, these tectonic mechanisms in one form or another, or in combination, are now believed to have provided the structural control for the origin of the WSB. Not yet comprehensively examined, however, is the role of non-tectonic processes in the formation of the WSB, as they may have influenced the size, configuration, subglacial sedimentation and subglacial topography of the WSB. In this paper we review the tectonic hypotheses and examine post-tectonic climate change along with glacial and marine processes as potentially significant factors in the present condition and configuration of the WSB. In the process, we find that there are a number of features not included in previous investigations that may have been major factors in the modification of the subglacial basin.